Pengaruh Pendapatan Per Kapita Dan Jumlah Penduduk Terhadap Konsumsi Di Provinsi Aceh - Maulana , Rio; Tarigan, Adelia Cintami Br; Chotimah, Nurul (Jurnal Samudra Ekonomika, 2024)
This research aims to determine the effect of per capita income and population on consumption in Aceh Province. The data used is time series data on per capita income, population and consumption levels for 2018-2022. The data analysis methods used are multiple linear regression analysis, t test, F test and coefficient of determination test. The regression equation in this study is Y = 1.229 + 0.391X1 + 0.559X2. Per capita income has a significant effect on consumption in Aceh Province, where from the t test the t sig value is obtained. < 0.05 (0.033 < 0.05). Population size has a significant effect on consumption in Aceh Province, where from the t test the t sig value is obtained. < 0.05 (0.020 < 0.05). Per capita income and population simultaneously have a significant effect on consumption inAceh Province, where from the F test the value of F sig is obtained. < 0.05 (0.020 < 0.05). From the coefficient of determination test, it can be explained that per capita income and population influence consumption in Aceh Province by 61.8% while the remaining 38.2% is influenced by other variables outside this research model.